Hallucinations and mental imagery demonstrate top-down effects on visual perception. (2016) - Howe, Piers D. L.; Carter, Olivia L.
Abstract: In this commentary, we present two examples where perception is not only influenced by, but also in fact driven by, top-down effects: hallucinations and mental imagery. Crucially, both examples avoid all six of the potential confounds that Firestone & Scholl (F&S) raised as arguments against previous studies claiming to demonstrate the influence of top-down effects on perception.